HISTOPATHOLOGICAL CHANGES OF THE UMBILICAL CORD IN COMPLİCATED PREGNANCIES - Seval Kaya (International Journal of Health Services Research and Policy, 2019)
Preeclampsia, hellp syndrome and gestational diabetes are quite common complication in pregnancy. In this study,ıt is aimed to compare the thickness of basal lamina and vascular structure of umbilical cord. by comparing preeclampsia, hellp syndrome, gestational diabetes and normal pregnant women. In the study, sanples were taken from postpartium umbilical cords of normal pregnant women, preeclampsia, gestational diabetes and pregnant women diagnosed with hellp syndrome. Umblical cord samples taken during maternity, followed by routine paraffin through fixing 10% neutral formalin. In this performed as totally sixty facts through taking fifteen umbilical cords from each of four groups, Hematoxyline-eosin, Masson trichrom, periodic acid Schiff, and toluidine blue stain were applied on to the serial histological sections obtained from paraffin blocks. The obtained slides were evaluated with Zeiss Imager 2 Microscope by taking micrographs. Morphometric measurements were statistically analyzed with SPSS software. In cases of gestational diabetes due to increased collagen production, thickening and excessive narrowing of the lumen and differentiation of Wharton jelly were observed in the umbilical artery. Differentiations are observed in the vacuolization of smooth muscle cells and muscle fibers that make up the media while camber and damage are observed in endothelial. The most significant structural changes of preeclamptic placentas are obtained as the thickening and the endothelial injury. In the umbilical cord artery medial layer, due to the growth of collagen fiber. In HELLP cases due to the increase in media diffuse edema between muscle fibers and in collagen, the thickening of umbilical artery wall and the narrowing of luminal are seen as extremely significant. Another striking symptom with HELLP cases is the observing of intramuscular hemorrhages in the umbilical artery wall as an unattained case in preeclampsia and gestational diabetes. In most of the cases, differentiation in Wharton jelly, metaplastic changes in the amniotic epithelium and thickening of the basal lamina are observed.